PENGARUH MEDIA WAYANG BERBASIS CERITA RAKYAT SI PAHIT LIDAH UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK PADA SISWA KELAS V SD NEGERI 227 PALEMBANG - Yuni Zahara; Yenny Puspita; Kiki Aryaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract, this study was conducted with the aim of determining whether or not there is an influence of puppet media based on the folklore of Si Pahit Tongue to improve listening skills in grade V students of SD Negeri 227 Palembang. The research method used is the experimental method. The type of research used in this study is using Pre-experimental design. The design used in this study is Pre-experimental design with the One - Shoot Case Study approach. The population and sample in this study were grade V students of SD Negeri 227 Palembang totaling 30 people with 28 boys and 12 girls. This study uses a saturated sampling technique. Data collection techniques through multiple choice tests. Data analysis techniques use normality tests, homogeneity tests, and hypothesis tests with the help of SPSS 25. Based on the results of the study and discussion, it shows that improving students' listening skills through folklore assisted by puppet media is more effective than applying conventional models. This is based on the results of the hypothesis test, a significance value of 0.002 < 0.05 is seen. So it can be concluded that the influence of puppet media based on the folk tale of Si Pater Tongue has an effect on improving listening skills in grade V students of SD Negeri 227 Palembang.